Bonding and Bridging Social Capital: The Performance of MSME Groups : JEL Classification: L26, M21, O17, Z13, R11 - Salma Rivani Luawo; Widya Kurniati Mohi (Journal La Bisecoman, 2026)
This study examines the utilization of social capital by members of the MSME group “H2 Rifal” in supporting their business performance. Two types of social capital serve as resources that enhance business performance. Bonding social capital refers to internal relationships or networks of family and relatives, which were utilized during the initial phase of business establishment. Meanwhile, bridging social capital refers to external relationships with various parties, which were utilized by H2 Rifal members during the business development stage. External relations with cooperatives, government institutions, and reseller agents have had positive impacts, providing various resources such as economic support, information, and educational assistance needed by group members. The research employs a descriptive qualitative method with six informants: (a) three group members who are business founders committed to running small enterprises in the pastry and cake production sector; (b) one reseller agent; (c) one staff member from the Social Affairs Office of North Gorontalo Regency; and (d) one staff member from the Cooperative and Trade Office of Gorontalo Province. The main contribution of this study is to emphasize the importance of social capital in the discourse on MSME empowerment. Business capital is not solely about financial capital but also includes non-economic capital. The argument concerning bonding and bridging social capital highlights that both are equally important as economic capital. Through the effective utilization of social capital, the H2 Rifal business group has demonstrated strong business performance, growth, independence, and sustained success over the past 20 years.